Trifkovič, Klavdija Čuček, Lorber, Mateja, Reljić, Nataša Mlinar, & Štiglic, Gregor (Eds.) (2023). Innovative nursing care: Education and research - Cheng, Fung Kei (Journal of Practical Nurse Education and Practice)

(untitled) (NorQuest College, 2025)
⁠⁠⁠⁠⁠⁠⁠An in-depth investigation into current nursing challenges and education is important for healthcare practitioners to provide professional services. The book being reviewed here discusses these topics comprehensively and inspires a person-centred approach to strengthening nursing care, which benefits not only relevant frontline workers, decision makers and researchers, but also patients and their family caregivers.